The regulation of the T-box transcription factor TBX3 in Luminal A breast cancer - Ncube, Stephanie Maria (Department of Human Biology, 2025)
Breast cancer is the second leading cause of death in women globally. This is in part due to poor therapy response, cancer cell drug resistance and the debilitating side effects associated with most therapies. There is therefore a need to improve current breast cancer therapy and/or to develop new and efficacious therapeutic drugs. One approach to addressing this has been to elucidate the molecular mechanism(s) underpinning this disease to identify key drivers that can be targeted in molecular therapies. To this end, the T-box transcription factor, TBX3, has been validated as a potential therapeutic target in breast cancer. TBX3 plays an important role in embryonic development including in the formation of several structures such as the heart, mammary glands, limbs, and lungs. Indeed, mutations in the human TBX3 result in ulnar mammary syndrome that is characterized by a range of clinical abnormalities, encompassing underdevelopment of the mammary and apocrine glands, as well as anomalies affecting the upper limb, areola, dental structures, heart, and genitalia. Although TBX3 has no known function in adult tissues it is frequently overexpressed in a wide range of cancers where it impacts several oncogenic processes including bypass of senescence, apoptosis and anoikis, promotion of proliferation, tumour formation, angiogenesis, invasion, and metastatic capabilities. In breast cancer, TBX3 is overexpressed in a subset of patient tissues and cell lines, and it promotes bypass of senescence, migration, and invasion and contributes to breast cancer stem cell expansion. Moreover, studies have shown that when TBX3 levels are depleted in breast cancer cells this inhibits migration, tumour formation and invasion. It has thus been validated as a potential therapeutic target in breast cancer. Transcription factors have, however, historically been regarded as ‘undruggable' and hence this study aims to identify more versatile and indirect ways of inhibiting the oncogenic activity of TBX3. To this end, this project investigates in breast cancer cells (1) the molecular mechanisms that upregulate TBX3, (2) TBX3 protein cofactors that regulate its oncogenic activity and (3) whether ID1 (inhibitor of differentiation 1) is transcriptionally activated by TBX3 to mediate its pro-migratory function in breast cancer. To elucidate the molecular mechanism(s) that upregulate TBX3 in breast cancer, this study hypothesised that it may involve the basic helix-loop-helix oncogenic transcription factor c-Myc because it has overlapping oncogenic roles with TBX3. Indeed, the constitutive activation of c-Myc has been widely reported to contribute to breast cancer progression and c-Myc-driven pathways are elevated in aggressive drug resistant breast cancer cells and tumours. In addition, c-Myc has previously been shown to directly bind and activate the TBX3 promoter at the E-boxes located at -1210 and -701 bps in chondrosarcoma and rhabdomyosarcoma cells. This study shows using qRT-PCR and western blotting, that when c-Myc is transiently depleted TBX3 mRNA and protein levels decrease. Importantly, when c-Myc is ectopically overexpressed in MCF-7 and T47D breast cancer cells in the presence of Actinomycin D, an inhibitor of de novo transcription, the ability of c-Myc to activate TBX3 mRNA levels is abolished. Together, these results suggest that c-Myc transcriptionally activates TBX3 in breast cancer cells. The AKT signalling pathway has been shown to contribute to uncontrolled proliferation, invasion and metastasis of breast cancer leading to poor prognosis. Three AKT serine-threonine kinase isoforms have been identified viz AKT1, AKT2 and AKT3 and elevated AKT1 and AKT2 kinase activity has been reported in 30-40% of oestrogen receptor-positive breast carcinomas. Given the overlapping oncogenic roles between AKT and TBX3 in breast cancer, and because TBX3 has previously been shown to be a substrate of AKT3 in melanoma and AKT1 in rhabdomyosarcoma, the AKT signalling pathway was of interest to this project. This study shows that inhibiting the AKT pathway in MCF-7 and T47D breast cancer cells using a commercially available AKT inhibitor as well as a dominant negative AKT results in a decrease in TBX3 protein levels. The regulation of TBX3 by AKT is shown to be a post transcriptional event as the inhibition of the AKT pathway has no effect on TBX3 mRNA levels. Moreover, AKT1 is shown to be the predominant AKT isoform in the breast cancer cell lines tested and the simultaneous inhibition of AKT1 and treatment with the proteosome inhibitor, MG132, rescued TBX3 levels. Lastly, cycloheximide chase assays and western blotting show that phosphorylation of TBX3 by AKT1 at Serine 720, stabilizes TBX3 in breast cancer cells, and mutating this site affects its ability to promote breast cancer cell migration. This suggests that the putative AKT target site S720 plays a role in regulating the pro-migratory role of TBX3 in breast cancer. To identify and characterize protein partners that interact and co-operate with TBX3 to promote breast cancer, MCF-7 breast cancer cell lines that stably express FLAG-TBX3 were firstly established to enable effective immunoprecipitation for mass spectrometry. The expression of FLAG-TBX3 was confirmed by western blotting and immunocytochemistry and the pro-migratory role of FLAG-TBX3 in breast cancer cells was confirmed using the two-dimensional in vitro scratch motility assay. Through affinity purifications coupled with mass spectrometry a myriad of putative TBX3 protein co-factors were identified and from this list Hsc70 and nucleolin were validated by immunoprecipitation and colocalization experiments in MCF-7 and T47D breast cancer cells. Importantly, results show that the interaction of TBX3 with Hsc70 is required for TBX3 protein stability and that nucleolin and TBX3 cooperate to promote MCF-7 and T47D breast cancer cell migration. ID1, a dominant-negative regulator of basic helix-loop-helix transcription factors, and key regulator of cancer progression has been identified as a TBX3 target gene that mediates its pro-migratory function in melanoma. Moreover, ID1 has been reported to promote breast cancer cell migration by regulating signalling pathways and factors involved in epithelial-mesenchymal transition (EMT) and cell motility. Whether TBX3 and nucleolin cooperate to transcriptionally activate ID1 in breast cancer is not known. This study shows using luciferase and chromatin immunoprecipitation assays that TBX3 and nucleolin cooperate to regulate ID1, through directly binding to a TBX3 full consensus T-element within the ID1 promoter. Furthermore, the study shows that treatment of MCF-7 and T47D breast cancer cells with the nucleolin targeting aptamer, AS1411, mislocalizes TBX3 and nucleolin to the cytoplasm and prevents them from activating ID1. Together the results from this study show that the c-Myc/AKT1/TBX3/Nucleolin/Hsc70/ID1 axis may be an important oncogenic pathway to target for the treatment of TBX3-driven breast cancer.